Rossby wave breaking, the upper level jet, and serial clustering of extratropical cyclones in western Europe - Priestley, Matthew D. K.; Pinto, Joaquim G.; Dacre, Helen F.; Shaffrey, Len C. (Geophysical Research Letters, 2017)
Winter 2013/14 was the stormiest on record for the UK and was characterized by recurrent clustering of extratropical cyclones. This clustering was associated with a strong, straight and persistent North Atlantic jet and was also associated with Rossby wave breaking (RWB) on both flanks, pinning the jet in place. The occurrence of RWB and cyclone clustering is further studied in 36 years of the ERA-Interim Reanalysis. Clustering at 55°N is associated with an extended and anomalously strong eddy-driven jet flanked on both sides by RWB. However, clustering at 65(45)°N has a dominance of RWB to the south (north) of the jet, deflecting the jet northward (southward). A positive correlation was found between clustering and RWB occurrence to the north and south of the jet. However, there is considerable spread in these relationships.